1998
DOI: 10.1007/s11357-998-0024-6
|View full text |Cite
|
Sign up to set email alerts
|

Effect of age on cytokine production in humans

Abstract: Aging is accompanied by many changes in immune response, with the most consistent and dramatic alterations occurring within the T cell compartment. Since cytokines are central to immune cell communications, age-associated changes in cytokine production may contribute to these alterations. While data from murine studies suggest a switch from a Th1 (IL-2, IFNγ) to a Th2 (IL-4, IL-6, IL-10) cytokine response, this model has not been as clearly established in humans. In addition, this current review of over 50 stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
2

Year Published

2003
2003
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 52 publications
1
20
2
Order By: Relevance
“…coli and HSV-1 concentrations that, in preliminary experiments, gave IL-6 levels that were approximately half way up the two dose response curves for maximal sensitivity. This is in keeping with Bernstein & Murasko’s finding that supraoptimal concentrations of stimuli tended to mask age-related differences in cytokine levels [ 30 ]. To monitor inter-assay variation we also included within every assay PBMCs that were frozen from healthy volunteers and tested with and without E .…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…coli and HSV-1 concentrations that, in preliminary experiments, gave IL-6 levels that were approximately half way up the two dose response curves for maximal sensitivity. This is in keeping with Bernstein & Murasko’s finding that supraoptimal concentrations of stimuli tended to mask age-related differences in cytokine levels [ 30 ]. To monitor inter-assay variation we also included within every assay PBMCs that were frozen from healthy volunteers and tested with and without E .…”
Section: Resultssupporting
confidence: 90%
“…Before embarking on studies to compare the levels of CI (at zero time values) and immune responsiveness to bacterial, viral and T cell challenges in young and old healthy volunteers, we set out to optimize our assays. Although both PBMCs and whole blood samples have been used in the literature [ 30 35 ], we chose to use whole blood samples since they have been shown to more closely mimic in vivo conditions [ 34 ], and had the advantages of fewer manipulations and presence of autologous plasma (which likely affects responses to ex vivo challenges), granulocytes and red blood cells [ 36 ]. To avoid the effects of diurnal rhythms [ 28 ] and diet [ 37 ] on cytokine secretion, all blood samples were taken between 8:30 am–10:00 am from overnight-fasted volunteers.…”
Section: Resultsmentioning
confidence: 99%
“…Aging is accompanied by many changes in immune response, with the most consistent and dramatic alterations occurring within the T cell compartment. Since cytokines are central to immune cell communications, age-associated changes in cytokine production may contribute to these alterations [28]. According to the present study, the level of IL-12 decreased with age, while other study demonstrated that the age was not significantly correlated with the serum IL-12 [29].…”
Section: Discussioncontrasting
confidence: 46%
“…So far, variation of cytokine production capacity in the general population has been investigated only in small studies, and this limitation resulted in conflicting conclusions (Aulock et al, 2006; Bernstein and Murasko, 1998; Grandgirard et al, 2013; Hwang et al, 2015; Nielsen et al, 2013; Scott et al, 2013). The only large scale studies of the immune system published to date are genome-wide studies focussed on the regulatory effect of genetic variation on cytokine gene transcription levels (eQTLs) rather than on protein expression levels (Berry et al, 2010; Fairfax et al, 2014; Lee et al, 2014; Raj et al, 2014; Ye et al, 2014).…”
Section: Introductionmentioning
confidence: 99%